Factors associated with in-hospital mortality after coronary artery bypass grafting in patients with CHD and type 2 diabetes - Aleksey Nikolaevich Sumin; Natalya Alexandrovna Bezdenezhnykh; Andrey Viktorovich Bezdenezhnykh; Sergey Vasil'evich Ivanov; Ekaterina Vladimirovna Belik; Olga Leonidovna Barbarash (Сахарный диабет)
Coronary artery bypass grafting (CABG) is the main method used for myocardial revascularisation in patients with diabetes mellitus (DM), and determining the factors affecting the outcomes of CABG in these patients is important. Objective. To identify risk factors for in-hospital mortality after coronary artery surgery (CABG) for patients with and without type 2 diabetes mellitus (T2DM). Methods. A retrospective analysis of the medical records of patients who underwent CABG from 2006 to 2009 was conducted. From these, 317 patients with T2DM were selected (median age: 59,0 years). As a control group, 350 patients (median age: 58,0 years) without diabetes or pre-diabetes, who were matched by sex, age and CABG characteristics, were selected. Logistic regression models were used to identify factors possibly associated with in-hospital mortality. Results. There were no group differences for the frequency of postoperative complications and in-hospital mortality (p >0,05). During the early postoperative period, 5 (1,6%) diabetic and 7 (2,0%) non-diabetic patients died (p=0,682). By the logistic regression analysis, T2DM did not predict patient mortality (p=0,458). Among the patients with T2DM, a risk of death was associated with a stroke history (OR 21,661; 95% CI 1,701-76,521; р=0,013), and a decreased glomerular filtration rate (GFR) as estimated by the CKD-EPI equation (OR 1,512 per 5 ml/min/1,73m2.  decrease; 95% CI 1,017-2,257; р=0,048), independent of gender, age or triple-vessel and left-main disease. By multivariate analysis for the non-diabetic patients, the risk of death increased by more than 10 times because of reinfarction (OR=10,272; 95% CI: 1,258?56,163; p=0,029) and increased by 6,8 times with an increase in preoperative fibrinogen levels of 1 g/l (OR=6,802; 95% CI: 1,283?35,714; p=0,024), independent of gender, age, smoking or mitral valve regurgitation. Conclusions. T2DM was not a predictor of death during the early period after CABG. For the diabetic patients, independent predictors of in-hospital mortality after CABG were stroke history and reduced GFR. For the patients without T2DM, the independent predictors were reinfarction and preoperative fibrinogen levels.